Effects of Dexmedetomidine on Basic Cardiac Electrophysiology in Adults; a Descriptive Review and a Prospective Case Study - Reino Pöyhiä; Teija Nieminen; Ville W. T. Tuompo; Hannu Parikka (MDPI AG, 2022)
Dexmedetomidine (DEX) is a commonly used sedative agent with no or minimal effects on breathing. DEX may also be beneficial in myocardial protection. Since the mechanisms of cardiac effects are not well known, we carried out a descriptive review and examined the effects of DEX on myocardial electrical conduction in a prospective and controlled manner. For the review, clinical studies exploring DEX in myocardial protection published between 2020-2022 were explored. A case study included 11 consecutive patients at a median (range) age of 48 (38-59), scheduled for elective radiofrequency ablation of paroxysmal atrial fibrillation. A bolus dose of DEX 1 µg/kg given in 15 min was followed by a continuous infusion of 0.2-0.7 µg/kg/h. Direct intracardiac electrophysiologic measurements, hemodynamics and oxygenation were measured before and after the DEX bolus. Experimental studies show that DEX protects the heart both via stabilizing cardiac electrophysiology and reducing apoptosis and autophagy after cell injury. The clinical evidence shows that DEX provides cardiac protection during different surgeries. In a clinical study, DEX increased the corrected sinus node recovery time, prolongated the atrioventricular (AV) nodal refractory period and cycle length producing AV nodal Wenckebach retrograde conduction block. DEX has a putative role in organ protection against hypoxic, oxidative and reperfusion injury. DEX slows down the firing of the sinus node and prolongs AV refractoriness.